Lakes of the Peace-Athabasca Delta: Controls on nutrients, chemistry, phytoplankton, epiphyton and deposition of polycyclic aromatic compounds (PACs) - Wiklund, Johan Andre (University of Waterloo, 2012)
Floodplain lakes are strongly regulated by river connectivity because floodwaters exert strong influence on the water balance, the physical, chemical and biological limnological conditions, and the influx of contaminants. The Peace-Athabasca Delta (PAD) in northern Alberta (Canada) is a hydrologically complex landscape and is an important node in the upper Mackenzie River Drainage Basin. The ecological integrity of the PAD is potentially threatened by multiple environmental stressors, yet our understanding of the hydroecology of this large floodplain remains underdeveloped. Indeed, ever since the planning and construction of the WAC Bennett Dam (1960s), concerns have grown over the effects of upstream human activities on the lakes of the PAD. More recently, concerns over the health of the PAD have intensified and come to the fore of national and international dialogue due to water abstraction and mining and processing activities by the rapidly expanding oil sands industry centred in Fort McMurray Alberta. Currently, widespread perception is that upstream human activities have reduced water levels and frequency of flooding at the PAD, which have lowered nutrient availability and productivity of perched basin lakes, and have increased supply of pollutants from oil sands. However, these perceptions remain based on insufficient knowledge of pre-impact conditions and natural variability. Current and past relations between hydrology and limnology of PAD lakes are mostly undocumented, particularly during the important spring freshet period when the effects of river flood waters are strongest. Similarly, knowledge of the deposition of oil-sands- related contaminants in the PAD remains insufficient to determine whether anthropogenic activities have increased the deposition of important oil-sands-related contaminants such as polycyclic aromatic compounds (PACs) relative to natural processes. Such knowledge gaps must be filled to achieve effective monitoring, policy and governance concerning impacts of industrial ...